Micromorphometric evaluation of changes in symmetry of sarcoplasmic reticulum membranes induced by vanadate - Kranzhöfer, Kristine; Agostini, Bruno; Martino, Luisa de; Hasselbach, Wilhelm (Zeitschrift für Naturforschung. C, a journal of biosciences, 1992)
Electron micrographs of light sarcoplasmic vesicles fixed with glutaraldehyde and osmium tetroxide followed by contrasting with uranyl acetate and lead citrate have been evaluated by registering their membrane profiles with a microdensitometer. The asymmetric arrangement of the two layers of the vesicular membrane could be ascertained by demonstrating a ratio of 1.5 for the thickness of the outer versus the inner membrane layer which is in general agreement with the proposed protein structure of the calcium transport enzyme. Treatment of the vesicles with low concentrations of vanadate (0.1 mM) results in a significant lowering of the symmetry ratio by 20% by reducing mainly the thickness of the outer membrane leaflet. Removal of the membrane lipids by treating the vesicles with phospholipase A 2 and bovine serum albumin diminishes the membrane surface by 50% resulting in a significant increase of both the membrane thickness and the asymmetry ratio by 30 and 12% respectively. The vanadate induced reduction of membrane asymmetry is accentuated after delipidation indicating that the membrane lipids are not essential for the asymmetric appearance of the native membrane. The stability of the spherical form of the vesicles to delipidation implies that the transport molecules are conically shaped allowing strong mutual interactions. At a measured height of the molecule of 80 Å in the membrane, the vanadate induced change in symmetry would be brought about by compensatory changes of less than 3 Å of the outer (35 Å) and the inner (25 Å) diameter of the cone.
Elektronische Reproduktion der Druck-Ausgabe 2. Juni 2014
Gesehen am 21.07.2025